RETRACTED: Examining the Relationship Between Product Market Competition and Chinese Firms Performance: The Mediating Impact of Capital Structure and Moderating Influence of Firm Size - Mubeen, Riaqa; Han, Dongping; Abbas, Jaffar; Raza, Saqlain; Bodian, Wang (Frontiers in Psychology, 2022)
This present study emphasized to reconnoiter the relationship between the Chinese companies' product market competition and organizational performance. This article explored the mediating effect of capital structure and the moderating impact of firm size in achieving a better performance of Chinese companies. This study employed a sample of 2502 Chinese firms' observations and identified that market competition positively influenced firm performance. Besides, capital structure partly mediated the relationship between product market competition and firm performance. Similarly, the present study also tested the moderating effect of firm size (both small and large) on the association between product market competition and firm performance. The results showed that large business firms' moderating effects significantly affect the nexus between product market competition and firm performance. Conversely, small firms' moderating role revealed a substantial adverse impact on the association between product market competition and firm performance. These findings contribute to the literature on the complex implications of market competition on business firms' performance. The results provide insightful and practical implications for future research directions.